The relationship of sociocultural beliefs and infertile couples' attitude toward reproductive donation: A descriptive-correlational study - Robab Latifnejad Roudsari; Hamideh Jafari; Ali Taghipour (Shahid Sadoughi University of Medical Sciences, 2019)
Abstract Background There are controversial views on accepting a reproductive donation in the world. Objective This study aimed to determine the relationship between the sociocultural beliefs and infertile couples' attitude toward reproductive donation in Mashhad, Iran. Materials and Methods This descriptive correlational study was conducted out on 115 infertile couples visiting Milad Infertility Center in Mashhad, Iran with using convenience sampling. The research instruments were valid and reliable sociocultural beliefs and attitude questionnaires, which were completed by the respondents on a self-report basis. Results The mean score of attitude toward reproductive donation in infertile women and men was 58.3 ± 12.6 and 57.8 ± 12.0, and the mean score of sociocultural beliefs in infertile women and men was 67.7 ± 11.5 and 67.6 ± 12.4, respectively. There was a direct correlation between sociocultural beliefs and attitude toward reproductive donation in infertile women (p < 0.001) and men (p < 0.001), that is, women and men with a higher score of sociocultural beliefs had a higher score of attitude as well. A direct correlation was also seen between sociocultural beliefs and infertile women and men's public attitude, their attitude towards genetic bound between parents and children, their attitude regarding the issue of confidentiality of the donation process, as well as attitude in relation to oocyte donation, embryo donation, and surrogacy (p < 0.001). Conclusion The findings suggest that sociocultural beliefs that surround reproductive donation could influence infertile couple's attitude toward accepting these therapeutic alternatives in infertile couples. It is therefore recommended to take steps to incorporate sociocultural beliefs into the routine care of infertile couples with the help of social media to give them ability for making more pragmatic decision in relation to their chosen options.